Parenting Style and Students' Career Maturity: The Mediating Role of Future Time Perspective - Yusran Sahodding; Mutmainnah Mutmainnah; Riyadlotus Sholichah; Yenti Arsin; M.Yunus Sudirman; Fitriyani Sulaiman (AL-ISHLAH: Jurnal Pendidikan, 2026)
Career maturity is a crucial component in preparing vocational students for successful school-to-work transitions. However, the role of parenting styles and psychological factors such as future time perspective (FTP) in shaping career maturity remains insufficiently understood, particularly in vocational education contexts. This study aimed to examine the direct effects of maternal and paternal parenting styles on students’ career maturity and to investigate the mediating role of FTP.This study employed a quantitative ex post facto design involving 307 students from nine vocational high schools in Enrekang Regency, Indonesia. Data were collected using the Parental Authority Questionnaire (PAQ), Career Maturity Inventory (CMI), and Future Time Perspective Scale (FTPS). Path analysis was conducted to assess direct and indirect relationships among variables.The results revealed that maternal parenting style (β = 0.45, p 0.01) and paternal parenting style (β = 0.61, p 0.01) significantly predicted career maturity. FTP also had a significant direct effect on career maturity (β = 0.44, p 0.01). Mediation analysis indicated that FTP significantly mediated the relationship between parenting styles and career maturity (maternal: β = 0.139, p 0.01; paternal: β = 0.136, p 0.01), suggesting both direct and indirect effects.These findings highlight the importance of supportive parenting and future-oriented thinking in enhancing students’ career readiness. Schools are encouraged to integrate career guidance programs that involve parents and strengthen students’ future time perspective to support effective career development.